Application of Geographic Information Systems in the Quantitative Analysis of Civil Defense Centers in the City of Basra - Muzafar Sahar Al-Kaabi , Assist. Prof. Dr. Murtadha (Basra studies journal, 2024)
Urban cities worldwide have been experiencing rapid urban growth, particularly in the twentieth and twenty-first centuries. This has led to a concentration of land use in very small residential neighborhoods, alongside high population density, making them prone to risks, disasters, and catastrophes due to the accumulation of flammable materials, as well as disturbances, terrorism, and wars in cities of developing countries. To address these challenges, civil defense agencies were established in urban areas to protect individuals, properties, and all service institutions from the dangers of disasters and wars, and to assist those affected. This research aims to study the services of civil defense centers in the city of Basra using quantitative and statistical analysis techniques available within the geographic information systems environment for the year 2023. The research reached several key findings, including: The initial establishment of Iraqi civil defense was in the 1940s, coinciding with World War II, particularly in 1942. The research revealed that there are eight civil defense centers serving the residents of Basra and its region. The study found that fire and rescue incidents have been steadily increasing due to various factors, with 696 incidents recorded in 2018, rising to 754 incidents in 2019, and further increasing to 979 incidents in 2020. The number of fire incidents continued to rise sharply, reaching 1,423 incidents in 2023.